Enhancing Game Development with Generative Artificial Intelligence Technologies: A Case Study of UNDO - Nunes, Eduardo Barroso; Rodrigues, Maria Andréia Formico (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2024)
This paper explores the use of Generative AI technologies in game development through the case study of the serious game UNDO, which integrates time-travel and environmental education. Players engage in recycling tasks to correct past environmental mistakes. By utilizing advanced AI technologies like ChatGPT-3.5, ChatGPT-4, GitHub Copilot, DALL-E 2, DALL-E 3, Midjourney, AudioLM, AIVA, SOUNDRAW, and ElevenLabs within Unity3D, UNDO demonstrates the potential of Generative AIs to enhance narrative, visuals, and audio. These tools facilitate content creation, enhance production efficiency, and reduce repetitive tasks, while still requiring human oversight for refinement. This study demonstrates Generative AI's effectiveness in enriching the game development process.